Effects of systemic Anatolian propolis administration on a rat-irradiated osteoradionecrosis model - Sefa ÇOLAK; Aras ERDIL; Fikret GEVREK (University of São Paulo, 2023)
Abstract Objective Radiotherapy after head and neck cancer is associated with the risk of osteonecrosis development. This study aims to investigate the effectiveness of systemic propolis application to prevent the disease as it has no definite treatment protocol despite the proposed treatment methods and significantly decreases individuals' quality of life. Methodology In total, 29 male Wistar-Albino rats were divided into control, 35 Gy irradiation (Group 1), 35 Gy irradiation+100 mg/kg/ml propolis administration (Group 2), and 35 Gy irradiation+200 mg/kg/ml propolis administration groups (Group 3). Propolis was first applied on the day after radiotherapy, except for the control group. Right first and second molars were extracted from all rats three weeks following radiotherapy. Samples were collected seven weeks after radiotherapy. Osteoblast and osteoclast counts were calculated by histomorphometric analysis. Immunohistochemical analysis determined bone morphogenic protein-2 (BMP-2) and transforming growth factor beta-3 (TGFβ-3). Results Group comparison found non-significant differences regarding osteoblast (p=0.130) and osteoclast (p=0.063) counts. However, Group 1 showed the lowest mean osteoblast (OBL: 82.63 [±13.10]) and highest mean osteoclast counts (OCL: 12.63 [±5.55]). OBL/OCL ratio showed significant differences between groups (p=0.011). Despite the significant difference between the Control and Groups 1 (p=0.006) and 2 (p=0.029), Group 3 showed a non-significant difference (p=0.091). For BMP-2 and TGFB3, the control group showed significant differences with the other two groups (p<0.001), except for Group 3. Conclusion Anatolian propolis showed beneficial effects in a radiotherapy-mediated osteonecrosis model, highlighting its potential as a promising intervention.